THE EFFECT OF NARRATIVE TEXT ON STUDENT'S ENGLISH READING COMPREHENSION - Hidayat, Tawvicky (Universitas Al-Amien Prenduan, 2017)
This study is aimed to study the effect of narrative text on student’s English reading comprehension. In this study, there are two research problems. The first, is there any effect of using narrative text on students’ reading comprehension in eight grade in SMPN 1 Pragaan Sumenep. The second, how significance does using narrative text effect on students’ reading comprehension in eight grade in SMPN 1 Pragaan Sumenep. The research population of this study is the eight grade students in SMPN 1 Pragaan Sumenep. It is containing 26 students. The writer takes all of the population as the sample of this study, namely 26 students. This study used test as main instrument. The tests were divided into pre-test and post-test. The supporting instruments are observation and documentation. The writer used statistical analysis as data analysis. The statistical formula which was used was t-test which was suitable with the research design, and it is one group pretest-posttest design. The research result shows that using narrative text effects the students’ reading comprehension in eight grade in SMPN 1 Pragaan Sumenep with sufficient significance. It is proven by the higher of value of to (4,7580) than the value of tt(2,06). It is also proven that the significance effect of using narrative text on students’ reading comprehension in eight grade in SMPN 1 Pragaan Sumenep is 95%, because the writer took the significant level of 5%. Based on the result of study, it can be concluded that using narrative text as a media in reading learning is very effective, especially in reading class. It is because the social function of narrative text is to amuse, and to entertain the reader. Then, it will make the readers enjoyable, and interested in reading, especially in junior high school.